2008
DOI: 10.5194/npg-15-631-2008
|View full text |Cite
|
Sign up to set email alerts
|

Short-term prediction of rain attenuation level and volatility in Earth-to-Satellite links at EHF band

Abstract: Abstract. This paper shows how nonlinear models originally developed in the finance field can be used to predict rain attenuation level and volatility in Earth-to-Satellite links operating at the Extremely High Frequencies band (EHF,. A common approach to solving this problem is to consider that the prediction error corresponds only to scintillations, whose variance is assumed to be constant. Nevertheless, this assumption does not seem to be realistic because of the heteroscedasticity of error time series: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Modelling results could be written as (15) and (16). 1 1 Fig. 3 is a forecasting results by the forecasting model given in this paper.…”
Section: Modelling Rain-induced Attenuation Time Seriesmentioning
confidence: 98%
See 3 more Smart Citations
“…Modelling results could be written as (15) and (16). 1 1 Fig. 3 is a forecasting results by the forecasting model given in this paper.…”
Section: Modelling Rain-induced Attenuation Time Seriesmentioning
confidence: 98%
“…The analysis results are listed in Table 2. It can be concluded that the forecasting model of the real-time dynamic characteristics rain-induced attenuation is ARIMA (1,1,6). Modelling results could be written as (15) and (16).…”
Section: Modelling Rain-induced Attenuation Time Seriesmentioning
confidence: 98%
See 2 more Smart Citations
“…ARIMA-GARCH model is implemented in many areas other than financial analysis for prediction and forecast purposes. It is used to predict electricity prices [17] and the rain attenuation level in Earth-to-Satellite links [18], both of them achieve good results. Some studies also apply the ARIMA-GARCH model to model and predict the computer network traffic, the results show that the model can capture prominent traffic characteristics and has better prediction accuracy [19]- [20].…”
Section: Introductionmentioning
confidence: 99%